Graphs in maritime transports - Dragomir, Cristina; Manole, Ionuț Constantin (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The rapid development of graph algorithms was primarily due to exponential progress known from the development of computers. Requested to participate in the process of combinatorial optimization, graphs¸ built a fund of theorems based on which a lot of algorithms have been developed that today form the toolbasic of this field. Applications of graph algorithms in various domains, from substantiating political decisions to macroeconomic issues, from production problems in the study of electrical networks, gives it an increased importance.